Evaluation of Information Technology Governance Maturity Level using COBIT 2019 in the Academic Information System at Nahdlatul Ulama University of Lampung - Hadi Nurma Dwi Saputra; Wasilah Wasilah (Universitas Islam Indragiri, 2026)
The rapid development of Information Technology (IT) has significantly facilitated human activities in carrying out work and various other tasks, including in the education sector. The utilization of IT plays an important role in supporting administrative processes and academic activities; therefore, proper governance is required to ensure its effective and efficient use. This study employed a descriptive quantitative approach. Data were collected through observation and the distribution of questionnaires to students. The sample size was determined using the Slovin formula with a 10% margin of error, resulting in a minimum required sample of 94 respondents. In total, this study successfully collected data from 108 student respondents. This research aimed to evaluate the maturity level of IT governance in the Academic Information System (SIAKAD) at Nahdlatul Ulama University of Lampung using the COBIT 2019 framework. The results indicated that the maturity level of SIAKAD governance was at level 4 (Predictable), meaning that the processes have been consistently implemented and well documented. The highest gap was found in the APO07 domain (Manage Human Resources), while the BAI03, DSS01, DSS02, and MEA01 domains showed stable performance in accordance with student expectations.